2018
DOI: 10.1093/jas/sky196
|View full text |Cite
|
Sign up to set email alerts
|

Effect of diet type and added copper on growth performance, carcass characteristics, energy digestibility, gut morphology, and mucosal mRNA expression of finishing pigs

Abstract: A total of 757 pigs (PIC 337 × 1050; initially 27.6 kg BW) were used in a 117-d experiment to determine the effects of added Cu from tribasic copper chloride and diet type on growth performance, carcass characteristics, energy digestibility, gut morphology, and mucosal mRNA expression of finishing pigs. Pens of pigs were allotted to 1 of 4 dietary treatments, balanced on average pen weight in a randomized complete block design with 26 to 28 pigs per pen and 7 replications per treatment. Treatments were arrange… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…Moreover, in the current study, the diets were formulated with premix containing 100 mg/kg Cu, which had exceeded the suggested supplemental level of copper source in EU (EU Regulation 2018/1039 suggested a copper source level of 25 mg/kg or lower for pigs after 20 kg). The high Cu feeding may lead to the overestimation of the DM and GE digestibility in diets, since previous research reported that the digestibility of DM and GE increased with the addition of Cu in the corn-soy diet [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, in the current study, the diets were formulated with premix containing 100 mg/kg Cu, which had exceeded the suggested supplemental level of copper source in EU (EU Regulation 2018/1039 suggested a copper source level of 25 mg/kg or lower for pigs after 20 kg). The high Cu feeding may lead to the overestimation of the DM and GE digestibility in diets, since previous research reported that the digestibility of DM and GE increased with the addition of Cu in the corn-soy diet [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Supplementation of Cu to diets increased lipogenesis and fatty acid uptake in fish, indicating that dietary Cu influences post-absorptive metabolism of lipids [157]. Copper supplementation in diets for finishing pigs did not affect mRNA transcription of intestinal CTR1 and FABP [158]. However, supplementation of Cu at 150 mg/kg in diets for growing pigs increased the abundance of lipoprotein lipase and FABP1 in the subcutaneous adipose tissue and liver, respectively [126].…”
Section: Growth Promoting Levels Of Coppermentioning
confidence: 99%
“…Cu supplementation at pharmacological doses (150-250 mg/kg, resulted in piglets' average body weight of 5.45 kg) improved growth performance and reduced the occurrence of diarrhea in weaned piglets [4,5]. Various studies have shown that high dietary Cu improves intestinal digestive and absorptive functions, which enhances growth performance, as the digestibility of energy, fat, and amino acids increases in pigs fed high Cu diets [6][7][8][9][10]. However, whether dietary Cu improves intestinal digestibility by affecting intestinal morphology is not clear because of the inconsistency of results.…”
Section: Introductionmentioning
confidence: 99%